Cash on the Table? Imperfect Take-up of Tax Incentives and Firm Investment Behavior - Wei Cui; Jeffrey Hicks; Jing Xing (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate whether investment incentives work in less developed countries by exploiting the introduction of accelerated depreciation (AD) for fixed asset investment in China as a natural experiment. In contrast to the large positive impact of similar tax incentives in the U.S. and U.K. found in recent studies, we document that AD was ineffective in stimulating Chinese firms' investment. Further, using confidential corporate tax returns from a large province, we find that firms fail to claim the AD benefit on over 80% of eligible investments. Firms' take-up is significantly influenced by their taxable positions and tax sophistication. Moreover, resources of local tax authorities help improve awareness of the policy. Our study contributes to the understanding of conditions under which tax incentives for investment can be effective.
Keywords: H20; H30; 330; tax incentives; investment; take-up; tax administration